A novel two-compartment barrier model for investigating nanoparticle transport in fish intestinal epithelial cells. Issue 2 (10th March 2016) - Geppert, Mark; Sigg, Laura; Schirmer, Kristin
Abstract : We introduce a novel in vitro rainbow trout intestinal barrier model and demonstrate its suitability for investigating nanoparticle transport across the intestinal epithelium. Abstract : We introduce a novel in vitro rainbow trout intestinal barrier model and demonstrate its suitability for investigating nanoparticle transport across the intestinal epithelium. Rainbow trout ( Oncorhynchus mykiss ) intestinal cells (RTgutGC) were grown as monolayers on permeable supports leading to a two-compartment intestinal barrier model consisting of a polarized epithelium, dividing the system into an upper (apical) and a lower (basolateral) compartment, and thereby mimicking the intestinal lumen and the portal blood, respectively. The cells express the tight junction protein ZO-1 and build up a transepithelial electrical resistance comparable to the in vivo situation. Fluorescent polystyrene nanoparticles (PS-NPs; average hydrodynamic diameter: 73 ± 18 nm) were accumulated by RTgutGC cells in a time-, temperature- and concentration-dependent manner. Uptake of PS-NPs was confirmed using fluorescence microscopy. Cells formed an efficient barrier largely preventing the translocation of PS-NPs to the basolateral compartment. Taken together, these data demonstrate the suitability of the in vitro barrier model to study the effects of nanoparticles in fish intestinal epithelial cells.